Exploring the implementation of an outreach specialist program for nursing home residents in Macao: A multisite, qualitative study - Zhifeng Cen; Junlei Li; Hao Hu; Hao Hu; Ka Cheng Lei; Cheng I Loi; Zuanji Liang; Tek Fai Chan; Carolina Oi Lam Ung; Carolina Oi Lam Ung (Frontiers Media S.A., 2022)
BackgroundThe "Specialist Medical Outreach Project (SMOP)" involving inter-disciplinary hospital-based healthcare professionals is a government initiative that aims to provide integrative specialist care to high-risk residents at the nursing homes. However, research exploring the implementation and impact of SMOP is lacking. This study aimed to evidence the impact of SMOP on the quality of care at the nursing home and the key contextual determinants influencing SMOP outcomes.MethodSemi-structured key informant audio-recorded face-to-face interviews were conducted with eight managers, six doctors, 28 nursing staff, and seven pharmacy staff at the nursing homes participating in the SMOP to collect insights about how SMOP was operated and performed, and the impact of SMOP as observed and expected. Participants were recruited with purposive sampling. A thematic analysis approach was employed and key themes were identified using open coding, grouping, and categorizing.ResultsForty-nine interviews were conducted. Thematic analysis identified three principal themes: the overall perception about SMOP, the benefits as observed; and the areas of improvement. Together with the 10 subthemes, the results highlighted the expectations for SMOP to address the unmet needs and promote patient-centered care, and the benefits of SMOP in supporting effective use of resources for the nursing home, reducing the risks of adverse events for the residents, promoting communication and capacity building for the healthcare providers and facilitating efficient use of healthcare resources for the health system. Requests for more frequent visits by a larger inter-disciplinary specialist team were raised. Careful staff and workflow planning, and mechanisms for data-sharing and communication across care settings were deemed the most important actions for improvement.ConclusionIt is a general perception that the SMOP is beneficial in enhancing the quality of care for high-risk residents in the nursing home in Macao. Cross-sector inter-disciplinary collaboration and efficient data-sharing and communication mechanism play a crucial role in ensuring the success of the program. A robust assessment framework to monitor and evaluate the cost-effectiveness of the program is yet to be developed.